Esoteric Islam in modern French thought: Massignon, Corbin, Jambet - Elmarsafy, Ziad (New directions in religion and literature, 2020)
Introducing the Guest -- 1. Louis Massignon: In the Beginning Was Desire -- 2. Henry Corbin: A Certain Vision -- 3. Christian Jambet's Resurrections -- Epilogue: One Being True to Oneself: Esoteric Authenticities -- Bibliography -- Index.